The Muslims of Buganda: a communography of the experiences and lives of the Baganda Muslims during the colonial period - McCollum, B (2023)
This dissertation examines the lives, experiences, and leadership of the Baganda Muslim community during the colonial period (ca. 1900 – 1962). Through an examination of the leadership of the Kibuli Muslim Community and how this group interacted with other Muslim communities within Buganda, this thesis analyses the ways in which the Baganda Muslims worked to navigate the marginalization they faced from the colonial state. This dissertation argues that the discrimination which the Muslims faced from their colonial government was multifaceted and was rooted in part in European fears of Islam and ideologies such as Islam noir. By analysing the colonial state’s approach to education, this thesis shows that educational policies were one of the central ways in which Muslims were marginalized during colonial rule. However, this dissertation also argues that the Muslims found and developed their own routes to educational attainment, working to negotiate the marginalization they faced from the anti-Muslim policies of the colonial government.